2009
DOI: 10.1016/j.biosystemseng.2008.10.009
|View full text |Cite
|
Sign up to set email alerts
|

A tractor-mounted scanning LIDAR for the non-destructive measurement of vegetative volume and surface area of tree-row plantations: A comparison with conventional destructive measurements

Abstract: The use of a low-cost tractor-mounted scanning Light Detection and Ranging (LIDAR) system for capable of making non-destructive recordings of tree-row structure in orchards and vineyards is described. Field tests consisted of several LIDAR measurements on both sides of the crop row, before and after defoliation of selected trees. Summary parameters describing the tree-row volume and the total crop surface area viewed by the LIDAR (expressed as a ratio with ground surface area) were derived using a suitable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
101
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(104 citation statements)
references
References 13 publications
0
101
0
3
Order By: Relevance
“…The use of TLS has gained wide attention in forest management and agriculture as an effective and non-destructive means of measuring, e.g., 3D-structure of trees and vegetation canopies (canopy gap fractions), tree volumes and leaf-area [3][4][5]. 3D modelling has become important in archaeology, e.g., building surveys and site models [6,7], where TLS is used to construct 3D models and create photorealistic virtual copies of landscapes, buildings, and archaeological features (see also [8]).…”
Section: Open Accessmentioning
confidence: 99%
See 2 more Smart Citations
“…The use of TLS has gained wide attention in forest management and agriculture as an effective and non-destructive means of measuring, e.g., 3D-structure of trees and vegetation canopies (canopy gap fractions), tree volumes and leaf-area [3][4][5]. 3D modelling has become important in archaeology, e.g., building surveys and site models [6,7], where TLS is used to construct 3D models and create photorealistic virtual copies of landscapes, buildings, and archaeological features (see also [8]).…”
Section: Open Accessmentioning
confidence: 99%
“…Furthermore, vehicle based systems are capable of faster and more effective data acquisition than the traditional stationary (multi-scan) laser scanning [21]. Further development and applications can also be expected in 3D city modelling (buildings and roads) [20,23], and agricultural studies [5].…”
Section: Open Accessmentioning
confidence: 99%
See 1 more Smart Citation
“…Cunha et al (2005) observed that one of the causes of product loss is spray volume that is inappropriate for specific crop characteristics. The crop canopy is one of the most important of these characteristics (ROSELL POLO et al, 2009). According to Viana et al (2010), uniform distribution within a specific diameter and using a specific number of droplets can lead to successful applications even at lower spray volumes.…”
Section: Introductionmentioning
confidence: 99%
“…Although the use of TLS intensity data as reflectance information has been proved to be effective to separate foliage from wood in trees and other applications [8,30], it is not useful to define a fixed set of filter parameters under the conditions of the present study. Intensities should be calibrated with an external reference if the aim is to develop an effective intensity-based filter.…”
Section: Discussionmentioning
confidence: 99%